On L_1 -weak ergodicity of non-homogeneous discrete Markov processes - Mukhamedov, Farrukh (IIUM Press, 2012)
In the present paper we investigate the L_1 -weak ergodicity of nonhomogeneous discrete Markov processes with general state spaces. Note that the L_1 -weak ergodicity is weaker than well-known weak ergodicity. We provide a necessary and sufficient condition for such In this processes to satisfy the L_1 -weak ergodicity.